Inteligência territorial e análise de recursos hídricos: apontamentos teórico-metodológicos aplicados ao diagnóstico e prognóstico do PSH - Celso Donizete Locatel; Adriano Lima Troleis; Larissa Sousa Mendes; Bruno Lopes da Silva (Confins)
This article discusses the application of territorial intelligence tools in the management of water resources, specifically regarding the diagnosis and prognosis of the Water Security Panel (PSH) project. The aim is to analyze some territorial intelligence strategies present in the documents that aim to improve water resource management in the context of the PSH. The methodological resources for the organization, processing, and representation of data in the PSH are presented, including the use of geoprocessing tools and information technology. Finally, the application of the SWOT matrix in each database used in the PSH is described, identifying the strengths, limitations, opportunities, and challenges related to the platform's functionalities. The discussion in these documents highlighted the importance of the PSH platform as a territorial intelligence tool, endowed with functions such as multivariate and interactive analysis of the elements of the Brazilian territory's water structure, enabling management actions, crossings, and links between different types of data, information, and scales.